Tradisi Baritan di Dusun Palulo Kabupaten Blitar: Kajian Living Hadis - Zahrotul Izzah; Fadli Azis Darmansyah; Rahmat Fithror Robi' (Universitas Ahmad Dahlan, 2022)
The Baritan tradition that occurs in Palulo hamlet, Blitar Regency is one of the traditions carried out by the Javanese people. This research examines the meaning of the Baritan Tradition according to local residents and relates the values ​​contained in it in the study of living hadith. The study of living hadith focuses on the traditional phenomenon of behavior that lives in society which is based on the hadith of the prophet. The research used is descriptive research that focuses on the baritan ceremony for the residents of Palulo Hamlet, Blitar Regency, East Java Province. Information collection methods used are library research, online research, observation or observation, as well as interviews with several informants. Based on this research, information is obtained that describes the interaction of living hadith through the ceremony. The implementation of the Baritan Tradition is an understanding of the values ​​that exist in society which is carried out together. Contribution of ideas, energy, modules related to the sustainability of the baritan ceremony. And the arrival at the Barıtan ceremony is a manifestation of this understanding.